Ex vivo and in vivo study of Kowa HA-2 applanation tonometer in the measurement of intraocular pressure in dogs - Andrade, Silvia Franco; De Andrade, Alexandre Lima [UNESP]; Kanashiro, Glaucia Prada; Silva, Danielle Alves; Barbero, Rafael Cabral; Kuhn, Jacqueline Marcussi Pereira; Da Silva, Andressa Caroline (Universidade Estadual de Londrina, 2016)
The objective of this study was to evaluate the use of the Kowa HA-2 applanation tonometer in measuring intraocular pressure (IOP) in dogs. Twenty eyes were used in an ex vivo study in which the calibration curve for manometry vs. tonometry was determined by artificially raising the IOP in 5 mmHg increments up to 60 mmHg (10-60 mmHg). Both eyes of 10 anesthetized dogs were studied in vivo to compare manometry vs. tonometry. In the ambulatory study, 168 healthy eyes, 74 eyes with glaucoma and 60 eyes with uveitis were evaluated by tonometry, which was performed with topical anesthesia and 1% fluorescein eye drops for the formation of fluorescein semicircles. The ex vivo study showed an excellent correlation coefficient (r2= 0.993) between the aneroid manometer and the Kowa HA-2 tonometer. In the in vivo study, there was no significant difference (P>0.05) between the IOP values by manometry and tonometry, showing the excellent accuracy of the Kowa HA-2 tonometer. In the ambulatory study using the Kowa HA-2 tonometer, the IOP values (mean±SD, in mmHg) were 15.1±1.8 (12.0 - 20.0) for the healthy eyes, 25.2±4.0 (20.0 - 38.0) for glaucomatous eyes and 10.1±2.3 (5.0 - 13.7) for eyes with uveitis. There was a strong correlation between the IOP values obtained by direct ocular manometry and those from the Kowa HA-2 tonometer. In the ambulatory study, the IOP values measured by the tonometer were compatible for healthy eyes and for eyes with glaucoma or uveitis. We conclude that Kowa HA-2 applanation tonometer is accurate and practical for IOP measurement in dogs.
Keywords: Applanation tonometer; Dogs; Glaucoma; Kowa HA-2 tonometer; Ocular manometry; Uveitis